The In-Vivo-Effect of E-Aminocaproic Acid (EACA) on Human Plasma Fibrinolytic System - Niewiarowski, St; Wołosowicz, Nina (Thrombosis and Haemostasis, 1966)
EACA was administered orally to 30 healthy volunteers in a single doses of 0.1 g per kg body weight. The level of this compound in blood plasma and its effect on the human plasma fibrinolytic system were investigated.EACA is rapidly absorbed from the intestinal tract, its maximal level in the blood plasma being reached one hour later. The half life of this compound in the blood plasma amounted to two hours on the average.The following changes in the plasma fibrinolytic system were observed : a) an inhibition of euglobulin fibrinolysis, which was most pronounced three hours after EACA ingestion ; b) a considerable increase in plasminogen, antiplasmin and antitrypsin activities (maximum-five hours after EACA) ; c) slight increase in fibrinogen level (maximum-five hours after EACA).The conclusion has been reached that EACA induces a rise in endogenous inhibitors of the fibrinolytic system in the normal organism which may reinforce the hemostatic effect of this drug. The observed phenomena may be explained if we assume that the activation of the fibrinolytic system in the organism is continuous.